KOMPUTASI DISTRIBUSI SUHU MENGGUNAKAN METODE LINE SUCCESSIVE OVERRELAXATION (LSOR) MELALUI PENDEKATAN BEDA HINGGA DALAM BAHASA PEMROGRAMAN MATLAB - Sarah Miriam (Universitas Lambung Mangkurat, 2011)
Abstract. The aim of this study is to design a computation program of thermal distribution by using the LineSuccessive Overrelaxation (LSOR) method through the finite difference approach in the language of MATLAB (MatrixLaboratory). The methodology used in this study is a literature study. The result of this study is a computation programthat can perform appropriately to show the thermal distribution of a two – dimension system in a steady state. Theoutput of the program is visualized by MATLAB in a contour graphic and a two – dimension graphic.Key words: Computation, thermal distribution, Line Successive Overrelaxation (LSOR), finite difference, MATLAB